Genome Reduction in the Mosquito Symbiont Asaia. (23rd November 2018) - Alonso, Diego Peres; Mancini, Maria Vittoria; Damiani, Claudia; Cappelli, Alessia; Ricci, Irene; Alvarez, Marcus Vinicius Niz; Bandi, Claudio; Ribolla, Paulo Eduardo Martins; Favia, Guido
Abstract: Symbiosis is now recognized as a driving force in evolution, a role that finds its ultimate expression in the variety of associations bonding insects with microbial symbionts. These associations have contributed to the evolutionary success of insects, with the hosts acquiring the capacity to exploit novel ecological niches, and the symbionts passing from facultative associations to obligate, mutualistic symbioses. In bacterial symbiont of insects, the transition from the free-living life style to mutualistic symbiosis often resulted in a reduction in the genome size, with the generation of the smallest bacterial genomes thus far described. Here, we show that the process of genome reduction is still occurring in Asaia, a group of bacterial symbionts associated with a variety of insects. Indeed, comparative genomics of Asaia isolated from different mosquito species revealed a substantial genome size and gene content reduction in Asaia from Anopheles darlingi, a South-American malaria vector. We thus propose Asaia as a novel model to study genome reduction dynamics, within a single bacterial taxon, evolving in a common biological niche.